Sustainability reporting, board gender diversity and earnings management: evidence from East Africa community - Githaiga, Peter Nderitu (Emerald, 2023)
Purpose The purpose of this study is to investigate the moderating effect of board gender diversity on the relationship between sustainability reporting (SR) and earnings management (EM) in the East Africa Community (EAC). Design/methodology/approach The study analyzed a sample of 71 publicly traded companies from 2011 to 2021. Findings The study finds that both SR and board gender diversity have a negative and significant effect on EM and that board gender diversity moderates the relationship between SR and EM. Practical implications The findings suggest that boards should support the adoption of SR and increase female representation as a practical way to reduce EM. Policymakers should also implement appropriate measures, such as imposing mandatory SR and gender quotas on corporate boards, to address EM. Originality/value This research adds to the limited knowledge of SR and EM in the EAC and also fills a gap in the existing literature by investigating the influence of board gender diversity on the link between SR and EM.